On the «Governmentality» Logic of International Criminal Rule of Law - Wang, He-yong; Wang , Qi-fei; Xiao , Sheng-le (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
As the liberal movement led by the United States and the West deepens, the rule of law is gradually spilling over from domestic to international domains. International criminal law, led by the International Criminal Court and based on judicial centrism, has become a recognized and necessary governance approach in the field of international criminal law. However, the selective justice and “appearance justice” that ignores and legitimizes the systemic forces behind violent crimes has sparked political discussions in the international community about the practical significance of international criminal law. This article focuses on liberal research advocating “international criminal rule of law” and its view of marginalizing state power through judicial governance and examines the governance logic of international criminal rule of law based on Michel Foucault’s governance theory. This article argues that international criminal law is a means for vested interests to dominate the global criminal field through international criminal law, rather than a means to constrain state power.